POLA PENERIMAAN SISWA TUNANETRA DALAM PEMBELAJARAN MATEMATIKA DI SMPLB - Nurmitasari, Nurmitasari (JURNAL E-DUMATH, 2015)
AbstractÂ The blind students have limitations in receiving information, they are only a hold of the senses of hearing and touch, so understanding of abstract mathematical objects understood through verbal description of teacher with concrete objects directly fingered. This can result in a lack of ability of students to accept the concepts being. The acceptance of blind students in understanding the concept of geometry, include: 1) the students attention to the teachers explanation; 2) the pattern of asking; and 3) the pattern of answers. Reception pattern blind students in understanding the concepts learned can be viewed through direct observation during the learning activities with the help of a data recording device handycame. The data has been analyzed through the stages of data reduction, data presentation and conclusion and validity of the data obtained by using triangulation time. The result showed that blind students have a pattern of acceptance in understanding the concept of geometry, as follows: 1) the students attention to the explanation of the teacher in the learning merely listened without linking with the previous concept; 2) the pattern command asks merely asking the teacher is less clear, which is not directly related to the concept studied; 3) the pattern of students in answering questions of teachers, obtained from the statements that have been previously informed.Â Keywords:reception pattern, blind students, mathematics learning